Model Alometrik Penduga Biomassa Semai Mangrove (Bruguiera gymnorrhiza) Di Kawasan Restorasi Budeng, Bali: Allometric Model for Estimating Biomass of Mangrove Seedling (Bruguiera gymnorrhiza) in Budeng Restoration Area, Bali - Utami, Revalina Sri; Subiyanto; Ismail, Moch. Rudyansyah; Sunarto; Sidik, Frida (HUTAN TROPIKA, 2025)
Currently, mangrove restoration and rehabilitation efforts are rampant through planting, but monitoring of these efforts has not been carried out properly because there is a major problem, namely the lack of monitoring methods. One of the monitoring methods that can be done is through biomass estimation as an indicator of mangrove growth. This study aims to develop an allometric model to estimate the biomass of Bruguiera gymnorrhiza mangrove seedlings as one of the mangrove species often used in planting. The method used in this study was the measurement of diameter and height of mangrove seedlings in the mangrove restoration area of Budeng Village, Jembrana. The data obtained were analyzed using regression analysis to produce an allometric model. The results showed that the resulting polynomial allometric model has a high level of accuracy in estimating mangrove vegetation biomass, by having a high coefficient of determination and a very small percentage error value. Therefore, the resulting polynomial allometric model with predictors of tip diameter and height diameter can be used as a tool to estimate mangrove seedling biomass in mangrove restoration areas.